2004
DOI: 10.1111/j.1479-8425.2003.00073.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered heart rate variability in severe sleep apnea syndrome

Abstract: Heart rate variability (HRV) was studied in 19 patients with severe obstructive sleep apnea syndrome (OSAS), 17 with mild OSAS and 19 control subjects. A very low frequency (VLF) component during sleep in frequency-domain analysis was significantly higher in patients with severe OSAS, but not in patients with mild OSAS, compared with controls. It suggests that VLF is useful for the screening of severe OSAS, but not for mild OSAS. In addition, a low frequency (LF) component during sleep was also elevated in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 5 publications
0
12
0
3
Order By: Relevance
“…The earliest study was from 1998 14 and the latest, 2017 15 . Those studies were from several different countries, such as Japan 14 , 16 , Sweden 17 , USA 18 , Greece 19 , Italy 20 , Turkey 21 , France 22 , Korea 23 , 24 , Spain 25 and China 15 . Six of them had controlled for additional factors such as medications intake and comorbidities.…”
Section: Resultsmentioning
confidence: 99%
“…The earliest study was from 1998 14 and the latest, 2017 15 . Those studies were from several different countries, such as Japan 14 , 16 , Sweden 17 , USA 18 , Greece 19 , Italy 20 , Turkey 21 , France 22 , Korea 23 , 24 , Spain 25 and China 15 . Six of them had controlled for additional factors such as medications intake and comorbidities.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with more severe OSAS exhibited a higher low frequency/high frequency (LF/HF) ratio, which reflects the balance between the sympathetic and parasympathetic nervous systems 13,14. Another study suggested that the marked rise in very low frequency (VLF) signal during sleep in severe OSAS patients, in contrast to the lack of such a change in mild OSAS patients, may represent a tool for determining the severity of OSAS 15. Narkiewicz et al reported that patients with moderate to severe OSAS had shorter RR intervals (defined as the time between two consecutive R waves in the electrocardiogram) and increased sympathetic burst frequency compared with control subjects 16.…”
Section: Introductionmentioning
confidence: 99%
“…Wakai ve ark. [21] ciddi TUAS'li 19, orta TUAS'li 17 hastada ve 19 sağlıklı bireyde, uyku sırasında KHD'yi frekans temelli analiz ile değerlendirmişler, VLF bileşeninin ciddi TUAS olan olgularda yüksek olduğunu saptamışlardır. Hafif TUAS olan olgular ile sağlıklı kontrol grubu arasında bir farklılık gözlenmezken, ciddi TUAS olan olgularda LF bileşenin de diğerlerine göre yüksek olduğunu kaydetmişlerdir.…”
Section: Polisomnografiunclassified
“…Anılan çalışmada, HF ve ULF için ise gruplar arasında belirgin bir farklılık ortaya çıkmamıştır. [21] Bulgularımız da bu çalışmanın bildirdiği sonuçlarla uyumludur.…”
Section: Polisomnografiunclassified
See 1 more Smart Citation